Didactic-pedagogical experiments on the aesthetics of domesticity and the language of the camera on the internet (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Based on a practical research carried out with students at the Federal University of Minas Gerais, this work aims to raise some reflections on the adaptation and displacement of certain didactic-pedagogical practices on theatrical scenography to the field of audiovisual language in the context of the internet. It is intended to share some brief examples of digital performances created by students, in which we sought to find points of contact between different domestic spatialities, and raise some questions about the aesthetics of domesticity appropriated by the language of the webcamera.
Keywords: Scenic space; Aesthetics of domesticity; Digital performance; Audiovisual language; Pedagogical didactic practices